Identification of Unique, Heterozygous Germline Mutation, STK11 (p.F354L), in a Child with an Encapsulated Follicular Variant of Papillary Thyroid Carcinoma within Six Months of Completing Treatment for Neuroblastoma. (July 2015) - Buryk, Melissa A.; Picarsic, Jennifer L.; Creary, Susan E.; Shaw, Peter H.; Simons, Jeffrey P.; Deutsch, Melvin; Monaco, Sara E.; Nikiforov, Yuri E.; Witchel, Selma Feldman
Papillary thyroid carcinoma (PTC) is rare in children, although it is a known secondary malignancy after treatment for neuroblastoma (NB). The interval between NB treatment completion and PTC is usually more than 5 years. A 4-year-old, female patient with a high risk adrenal NB was found to have a 2.9-cm, right thyroid nodule on surveillance chest computed tomography (CT) 6 months after completion of her NB treatment (induction chemotherapy, tumor resection, autologous stem cell transplantation, external beam radiation to the abdominal tumor site, immunotherapy, and retinoic acid). Posttreatment surveillance included iodine-123-metaiodobenzylguanidine scans and CT scans. Fine-needle aspiration of the thyroid nodule diagnosed a follicular neoplasm, which was negative for BRAF, NRAS, KRAS, HRAS, PAX8/PPARg, and RET/PTC mutations, without evidence of metastatic NB. Nodule histology demonstrated an encapsulated follicular variant of PTC (FVPTC). Next-generation sequence analysis for a 46 cancer-gene profile was performed on both tumors with subsequent peripheral blood DNA testing. A heterozygous missense mutation in STK11 (F354L) was identified in both the NB and FVPTC. This mutation was also detected in peripheral blood mononuclear cells. Two additional heterozygous somatic missense mutations of uncertain significance were identified: KDR/VEGF receptor 2 (Q472H) on chromosome 4 and MET (N375S) on chromosome 7. To our knowledge, this is the shortest reported duration from completion of NB treatment to detection of thyroid cancer. The association of the STK11 gene with Peutz-Jeghers syndrome, lung adenocarcinomas, and medullary thyroid cancer leads to a possible association between this genetic variant and our patient's tumors.